ANALISIS DETERMINAN PRODUK DOMESTIK BRUTO INDONESIA PERIODE 2000-2021 - Putra Ario Wibowo (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2023)
Gross Domestic Product is an indicator of successful economic growth. Indonesia's economic growth as a developing country is quite good because it has accelerated from year to year. This study aims to determine the effect of exports, labor, foreign debt, inflation, and investment in the economic sector on Indonesia's Gross Domestic Product. This type of research is a quantitative research using secondary data. Data used from 2000-2021. The data analysis technique used is multiple linear regression (Multiple Regression Analysis Model). The results of the analysis show that the variables that have a significant influence on Indonesia's GDP are exports, labor and investment in the economic sector. Meanwhile, foreign debt and inflation variables have no effect on Indonesia's GDP. The condition of Indonesia's GDP when viewed from the results of the study will increase with better export values and an increase in labor, as well as increased investment in targeted economic sectors.